2000
DOI: 10.4049/jimmunol.164.10.5010
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Stromal Cell-Derived Factor-1 Is a Costimulator for CD4+ T Cell Activation

Abstract: Stromal cell-derived factor (SDF)-1 is a chemoattractant for T cells, precursor B cells, monocytes, and neutrophils. SDF-1α was also found to up-regulate expression of early activation markers (CD69, CD25, and CD154) by anti-CD3-activated CD4+ T cells. In addition, SDF-1α costimulated proliferation of CD4+ T cells and production of IL-2, IFN-γ, IL-4, and IL-10. Stimulation with SDF-1α alone did not induce activation marker expression, proliferation, or cytokine production by the CD4+ T cells. SDF-1α-mediated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
152
0
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 181 publications
(166 citation statements)
references
References 30 publications
11
152
0
3
Order By: Relevance
“…B cells from different developmental stages, e.g., developing bone marrow B cells (36), B cells leaving GC structures (33), and medullary plasmablasts leaving lymph nodes (34), have been found to express high levels of surface CXCR4 but were unresponsive to CXCL12. In this regard, there is some evidence that CXCR4 might fulfill additional functions besides chemotaxis, e.g., cell growth, proliferation, and transcriptional activation (11,33,37,38). In accordance, CXCL12 treatment has been found to increase NF-B activity in nuclear extracts from CXCR4-transfected murine pre-B lymphoma cells (37).…”
Section: Discussionmentioning
confidence: 90%
“…B cells from different developmental stages, e.g., developing bone marrow B cells (36), B cells leaving GC structures (33), and medullary plasmablasts leaving lymph nodes (34), have been found to express high levels of surface CXCR4 but were unresponsive to CXCL12. In this regard, there is some evidence that CXCR4 might fulfill additional functions besides chemotaxis, e.g., cell growth, proliferation, and transcriptional activation (11,33,37,38). In accordance, CXCL12 treatment has been found to increase NF-B activity in nuclear extracts from CXCR4-transfected murine pre-B lymphoma cells (37).…”
Section: Discussionmentioning
confidence: 90%
“…It was previously reported that activated T cells express CD154 and ICOS (34,35). We used flow cytometry to analyze CD154 and ICOS expression on peripheral blood and synovial CD4 and CD8 T cells from patients with RA.…”
Section: Expression Of Cxcr6 By Cd4 and Cd8 T Cellsmentioning
confidence: 99%
“…IL-2 will induce the expression of CCR5 on human T cells of the memory phenotype, mediating a positive feedback for CCR5 expression [12]. CXCL12 (SDF-1␣) will also costimulate human CD4 positive T cells, implying that T cell stimulatory activity is exhibited by different chemokines [13]. As for CCR5, membrane-associated lipid rafts are important for CXCL12-CXCR4 binding and signaling [14].…”
Section: Chemokines Are (Co)stimulatory For T Cellsmentioning
confidence: 99%